INCORPORATING WAYANG BEBER AS ENGLISH TEACHING MATERIALS TO PROMOTE ISLAMIC VALUES IN BUILDING STUDENTS’ CHARACTERS - Fitri, Okta Maya (STAI Ma'had Aly Al-Hikam Malang, 2024)
Integrating English language teaching with cultural contents is significantly pivotal in preserving its values of the local culture. Ironically, it has not gained much attention regarding the integration of Pacitan’s local wisdom in English language teaching. Furthermore, English language teaching involves learning not only grammar and vocabulary, but it is also essential to learn about cultures. Additionally, enhancing students’ character development by merging local wisdom into English learning materials can promote Islamic values to safeguard the harmony and tolerance in local community. Wayang Beber, as one of Pacitan’s local wisdoms, stipulates that its values can both enrich educational contents and encourage essential character traits among students. This paper employs library research to gain deep understanding about the depiction of Wayang Beber as one of learning materials utilized in English language teaching. The results of the research denote that integrating local culture, Wayang Beber, not only the local culture can be preserved but also learning materials can be more various and interesting.